Calcio sérico y su relación con la hipertensión inducida por el embarazo en gestantes que cursan el segundo y tercer trimestre, atendidas en el Hospital Isidro Ayora - Granda Vera, Margeory, Katerine (2016)
The arterial hypertension complicates the 8 to 10% of pregnancies, being important cause of maternal and fetal morbidity and mortality. Although this disease is very common, its pathogenesis is unknown, but studies indicate that calcium plays an important role in regulating blood pressure. To understand the behavior of calcium in hypertensive disorders, a descriptive cross-sectional study was conducted at the Isidro Ayora Hospital in the city of Loja, in order to determine the relationship between serum calcium levels and pregnancy-induced hypertension. They were subjected to the study 60 pregnant women enrolled in the second and third trimester, to which they took a sample of venous blood which were made a venous blood sample, same that were processed in an automatic analyzer by photometric method. Then we proceeded to relate the values of blood pressure that was extracted from the medical records of each patient with calcium levels obtained, can identify normal calcium levels by 65%, diminished 26.7% and increased 8.3%. It was possible to show 16 pregnant women with decreased levels of calcium, of which the 43.75% (n=7) present increased blood pressure. Keywords: Pregnancy induced hypertension, calcium, pregnancy.